Development and validation of the coach's task presentation scale: A quantitative self-report instrument. (July 2016) - Tristán, José Leandro; López-Walle, Jeanette Magnolia; Tomás, Inés; Cantú-Berrueto, Abril; Pérez-García, José Alberto; Castillo, Isabel
Abstract: Objective: A major concern for coaches is the transmission of effective information in the moments before sport practice, when they communicate to players what they are supposed to do and how (Rink, 1994). The present study's main objective was to cover a gap in the sport psychology measurement field and to develop and validate a quantitative self-report instrument to measure the effectiveness of coaches' task presentation for athletes. The resulting instrument was the Escala de Presentación de las Tareas por Parte del Entrenador (EPTE ) [Coach's Task Presentation Scale]. Design: The two studies developed to validate the EPTE used a cross-sectional research design. Method: Participants in Study 1 included 830 college athletes aged between 18 and 27, who completed the EPTE. Participants in Study 2 included 677 college athletes aged between 17 and 29, who completed the EPTE and other questionnaires measuring coach's interpersonal style (autonomy support and controlling style) and basic psychological needs satisfaction/thwarting. Study 1 comprised translation, item formulation and examination of the reliability and factorial structure of the EPTE. Study 2 provided evidence of factorial validity and evidence of validity based on relationships with other variables in the context of the Self Determination Theory (Deci & Ryan, 2000). Results: The results of reliability analysis and the different sources of validity provided, demonstrated the instrument's adequacy in terms of psychometric properties. Conclusions: The EPTE is a valid, reliable scale that can be used to measure the effectiveness of task presentation by coaches, according to the perception of athletes. Highlights: Gap in measurement of structure before the activity in sport psychology is covered. Development of self-report measure for effectiveness of coaches' task presentation. Coach's Task Presentation Scale (EPTE) showed adequate psychometric properties. Evidence of factorial validity and measurement invariance across gender for EPTE. Support to EPTE's relationship with variables studied by SDT in the sport context.